2004
DOI: 10.1029/2003wr002836
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental questions about water rights and market reallocation

Abstract: [1] Water markets have many advantages for water reallocation. However, water markets do not always function efficiently because the property rights structure was not designed for market transactions. The potential for successful markets can be determined by looking at the 10 fundamental questions relevant to water rights. The questions are relevant to any system of water rights, but the examples used are largely from the western United States. The questions are designed to raise issues about the basic structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 7 publications
1
27
0
1
Order By: Relevance
“…There, systems of transferable water rights have improved the efficiency of water use, but are new and remain imperfect (Dinar and Mody, 2004;Matthews, 2004;Pigram, 1999;Smith, 1998) and have to be very carefully tailored to local institutional and environmental conditions (Haddad, 2000b). Yet, even if this policy instrument works in some countries, it will not necessarily work in China: externally driven solutions to water problems in developing countries tend to correct the least relevant problems in the least practical way (Biswas, 2001;Pigram, 1999).…”
Section: Article In Pressmentioning
confidence: 98%
“…There, systems of transferable water rights have improved the efficiency of water use, but are new and remain imperfect (Dinar and Mody, 2004;Matthews, 2004;Pigram, 1999;Smith, 1998) and have to be very carefully tailored to local institutional and environmental conditions (Haddad, 2000b). Yet, even if this policy instrument works in some countries, it will not necessarily work in China: externally driven solutions to water problems in developing countries tend to correct the least relevant problems in the least practical way (Biswas, 2001;Pigram, 1999).…”
Section: Article In Pressmentioning
confidence: 98%
“…However, Matthews (2004) argues that water markets do not function efficiently as water property rights were not designed for market transactions. The author raises several issues regarding the structure of a water right system driven by the experience in the western United States.…”
Section: Introductionmentioning
confidence: 99%
“…In an administered system, water rights trading is fully planned for achieving the overall optimal benefits [19]. Matthew et al [20] suggested that water markets do not often function efficiently in practice, because self-interest is the main issue in the water rights trading market. Calatrava et al [21] showed that centralized water markets lead to more efficient water resources allocation and utilization than that of decentralized markets.…”
Section: Introductionmentioning
confidence: 99%